Integrating hybrid nanofluid on bioconvection flow for a Brinkman type fluid in channel - Wan Nura’in Nabilah Noranuar; Ahmad Qushairi Mohamad; Fasihah Zulkiflee; Lim, Yeou Jiann; Sharidan Shafie; Noraihan Afiqah Rawi; Vieru, Dumitru; Khan, Ilyas (Penerbit Universiti Kebangsaan Malaysia, 2025)
With the escalating global water crisis, carbon membrane technology presents a promising solution for purifying both water and wastewater. Titanium oxide nanoparticles 2()TiO are commonly incorporated to enhance membrane performance, offering significant advantages in water treatment systems due to their multifunctional properties, such as improved adsorption, catalytic activity, and antimicrobial effects. By combining 2 TiO with carbon in a hybrid membrane, the limitations of using metal or carbon catalysts alone are effectively addressed. This article mathematically simulates the performance of a hybrid membrane in water treatment systems by deriving the governing equations for the bioconvection flow of a Brinkman-type fluid, taking into account the effects of hybrid nanoparticles. The simulation is conducted within a channel under appropriate initial and boundary conditions, which are then transformed into dimensionless form using dimensionless variables. Analytical solutions are obtained with the help of the Laplace transform method. The results indicate that as the volume fraction of hybrid nanoparticles increases, both fluid velocity and microorganism profiles decrease, while temperature profiles exhibit the opposite effect. These findings align with experimental evidence supporting the integration of hybrid nanomaterials in water treatment technologies, ultimately enhancing the efficiency of the treatment process.